IMPOLITENESS USED BY HATERS ON INSTAGRAM COMMENTS OF MALE-FEMALE ENTERTAINERS - Suci Erza; Hamzah Hamzah (English Language and Literature, 2018)
This study aims to analyze the strategy of impoliteness used by haters on instagram comment artists using pragmatic approach. The purpose of this study was to find the type of impoliteness strategy used by hater on instagram artists. The data was taken from the comments contained in the instagram lambe_turah account. Lambe _turah account is an instagram account which is now very popular among the people because it concerns the artist's daily life. In addition, this study also analyzed the comparison between male artists and female artists based on the types of impoliteness strategies proposed by Culpeper (1996). The results of this analysis showed that from 200 comments of male and female artists. From the analysis, the writer found 5 strategies of impoliteness, namely (1) bald on record impoliteness, (2) positive impoliteness. (3) Negative impoliteness, (4) sarcasm or mock politeness, (5) withhold politeness. The most used strategies by all comments were positive impoliteness. The highest user of positive impoliteness was Alghazali. It found (32%) on his data. Meanwhile, in Prilly data this strategy found about (28%) on her data as the last most user of impoliteness.